Peningkatan Kemampuan Pemecahan Masalah Matematis Siswa SMA Melalui Model Pembelajaran Kooperatif Tipe GI Dan LAPS – Heuristik: Studi Komparatif Model Group Investigation dan Logan Avenue and Problem Solving - Heuristik - Febi Yolanda Sanaki (LPPM Universitas Advent Indonesia, 2020)
This research is a comparative study that aims to compare the improvement of students' mathematical problem-solving abilities with two different learning models. The sample of this study was two classes at Pasundan 8 Bandung High School, class XI IPA 1 and XI IPA 3, respectively. The instrument used was a test of problem-solving skills in the form of problem descriptions and student response questionnaires. The results of this study are (1) Improvement of mathematical problem-solving abilities of students who obtain learning with the Group Investigation and Logan Avenue Problem Solving (LAPS) - Heuristics model is in the medium category. (2) There is a significant difference in the improvement of mathematical problem-solving abilities between students who obtain the Group Investigation learning model and students who obtain the Logan Avenue Problem Solving (LAPS) - Heuristic learning model. (3) The students are in favor to learn mathematics using the Group Investigation (GI) learning model and Logan Avenue Problem Solving (LAPS) - Heuristics.